Kesalahan Ustaz dalam Bahasa Arab Verbal pada Penyampaian Materi Dakwah Islam - Mushodiq, Muhamad Agus; Syaifullah, Muhammad; Amalia, Dian Risky; Izzah, Nailul; Pratiwi, Bety Dwi (Institut Agama Islam Negeri Curup, 2021)
This paper aims to reveal the mistakes of micro Arabic in the aspects of Ilm Saut (phonology), Sharaf (morphology), Nahw (Syntax), and 'Ilm Dalalah (Semantics) in preaching materials conveyed by ustadz and ustadzah included in the groups of